2003
DOI: 10.1046/j.1365-3156.2003.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the entomological inoculation rate for Ifakara: a semi‐urban area in a region of intense malaria transmission in Tanzania

Abstract: SummaryAn entomological study on vectors of malaria and their relative contribution to Plasmodium falciparum transmission in the semi-urban area of Ifakara, south-eastern Tanzania, was conducted. A total of 32 houses were randomly sampled from the area and light trap catches (LTC) performed in one room in each house every 2 weeks for 1 year. A total of 147 448 mosquitoes were caught from 789 LTC; 26 134 Anopheles gambiae s.l., 615 A. funestus, 718 other anophelines and 119 981 culicines. More than 60% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 29 publications
(56 reference statements)
3
111
2
Order By: Relevance
“…It is now apparent that, owing to ongoing malaria control activities and urbanization, there has been a sustained decrease in transmission in this area in the last decade . A recent study reported an EIR of as low as 29 (95% CI 19-44) bites per annum (Drakeley et al, 2003). As a consequence of the lower transmission rate our study had less power than expected and even the oldest children in our study had experienced much less P. falciparum exposure than those children elsewhere in whom multiple infections appeared to be protective (Al Yaman et al, 1997a;Beck et al, 1997;Contamin et al, 1996;Farnert et al, 1999;Robert et al, 1996).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It is now apparent that, owing to ongoing malaria control activities and urbanization, there has been a sustained decrease in transmission in this area in the last decade . A recent study reported an EIR of as low as 29 (95% CI 19-44) bites per annum (Drakeley et al, 2003). As a consequence of the lower transmission rate our study had less power than expected and even the oldest children in our study had experienced much less P. falciparum exposure than those children elsewhere in whom multiple infections appeared to be protective (Al Yaman et al, 1997a;Beck et al, 1997;Contamin et al, 1996;Farnert et al, 1999;Robert et al, 1996).…”
Section: Discussioncontrasting
confidence: 63%
“…A decade ago, the average entomological inoculation rate (EIR) recorded in nearby rural areas was more than 300 infectious bites per person per year (Smith et al, 1993). However, recent field surveys have found much lower levels of malaria transmission, in particular in Ifakara town where an annual EIR of 29 infective bites per person has been estimated (Drakeley et al, 2003). Ifakara town is the site of the St Francis Designated District Hospital (SFDDH), which provides primary health care facilities for the population of the town, as well as acting as a referral hospital for the whole district.…”
Section: Study Sitementioning
confidence: 99%
“…An. marajoara was the most abundant species in the study area although its man-biting rate was only 1.27 bites/person/night (Table), which is lower than the biting rates (5.2-31.1) previously reported for this species in Western Venezuela (Rubio- (Drakeley et al 2003); c: mean caught per night by 2 human baits + 3 CDC light traps + 3 UV light traps (number of nights = 121). Three light traps = 1 human bait (Moreno et al 2002); d: biting rate x sporozoite rate x 365; e: other species, includes Anopheles braziliensis, Anopheles oswaldoi and Anopheles triannulatus; EIR: entomological inoculation rates.…”
Section: Discussionmentioning
confidence: 52%
“…To compare the observed differences in sporozoite rates between anopheline species, the confidence intervals were calculated according to the limits of expectations of binomial distributions (Drakeley et al 2003). The program StatXact ® (version 8: Cytel Inc 2007) was used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of the EIR differ in predictable ways, depending on the methodology and frequency with which human biting rate and sporozoite rate are measured 39,40,[44][45][46][47] . An additional explanation for the variability is that the efficiency of transmission differs among vector species 48 .…”
Section: Discussionmentioning
confidence: 99%